Manipulation of GameXPeptide synthetase gene expression by a promoter exchange alters the virulence of an entomopathogenic bacterium, Photorhabdus temperata temperata, by modulating insect immune responses - Jin, Gahyeon; Hrithik, Md Tafim Hossain; Lee, Dong-Hee; Kim, Il-Hwan; Jung, Ji-Seon; Bode, Helge B.; Kim, Yonggyun (Frontiers in Microbiology, 2023)
An entomopathogenic bacterium, Photorhabdus temperata subsp. temperata, is mutualistic to its host nematode, Heterorhabditis megidis. The infective juvenile nematodes enter target insects through natural openings and release the symbiotic bacteria into the insect hemocoel.The released bacteria suppress the insect immune responses and cause septicemia by their secondary metabolites. GameXPeptide (GXP) is one of the common secondary metabolites of most Photorhabdus species and is produced by the catalytic activity of a specific non-ribosoma l peptide synthetase called GxpS encoded by the gxpS gene. This study confirmed gxpS to be encoded in the P. temperata temperata genome and analyzed its expression during bacterial growth. LC-MS/MS analysis of the bacterial culture broth contained at least four differe nt GXPs (GXP-A  GXP-D), in which GXP-A was the most abundant. To investigate GXP synthesis following gxpS expression, the gxpS promoter of P. temperata temperata was replaced with an inducible arabinose promoter by homologous recombination. The gxpS transcript levels in the mutant were altered by the addition of L-arabinose. Without the inducer, the gxpS transcript level was significantly lower compared to the wild type and produced significantly lower amounts of the four GXPs. The addition of the inducer to the mutant significantly increased gxpS expression and produced significantly higher levels of the four GXPs compared to the wild type. The metabolite extracts obtained from wild type and mutant bacteria showed differential immunosuppressive activities according to their GXP contents against the cellular and humoral immune responses of a lepidopteran insect, Spodoptera exigua.Interestingly, the gxpS-mutant bacteria showed less insecticidal activity compared to the wild type, whereas addition of GXP to the mutant significantly restored insecticida l activity. These results suggest that the gxpS gene encoded in P. temperata temperata is responsible for the production of at least four different GXPs, which play crucial roles in the bacterial virulence.